PENGARUH KOMPETENSI SDM DAN MOTIVASI TERHADAP KINERJA PEMILIK UMKM SEKTOR KULINER DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - ,Arwinence Pramadewi, Silvia Andini , Jumiati Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of HR competence and motivation on the performance of UMKM owners in the culinary sector in Marpoyan Damai District, Pekanbaru City. The population in this study were UMKM owners in the culinary sector in Marpoyan Damai District, Pekanbaru City, namely 1,438 UMKM owners. The sampling technique in this study used the slovin formula, namely 93 UMKM owners. The data source used is primary data collected by distributing questionnaires as a research instrument. and the analysis tool is multiple linear regression analysis through the SPSS For Windows 25 program. With the performance of UMKM owners as the dependent variable and two independent variables, namely HR competency and motivation variables. The results of this study indicate that: 1) HR competence has a significant effect on the performance of UMKM owners, 2) Motivation has a significant effect on the performance of UMKM owners and 3) HR competence and motivation have an effect on the performance of UMKM owners. Keywords: HR Competence, Motivation, Performance of UMKM Owners